Changes in behavioral outcomes among children affected by HIV: Results of a randomized controlled trial in China. (September 2019) - Li, Li; Liang, Li-Jung; Lin, Chunqing; Lan, Chiao-Wen; Ji, Guoping; Xiao, Yongkang
This study assessed the effects of a multilevel intervention on HIV-affected children's negative behaviors. A total of 536 children aged 6–18 years from 475 HIV-affected families in Anhui, China, participated in the randomized controlled trial. A significant overall intervention effect on reducing negative behaviors was observed at 18-month follow-up, and the effect remained at 24-month follow-up. The intervention showed greater effects for children aged 13–18 years than those aged 6–12 years. Study findings suggest that a multilevel intervention approach could be beneficial for reducing negative behavior in HIV-affected children. Age-specific programs should be considered to maximize the intervention effects.